Attitudes of mothers and health care providers towards behavioural interventions promoting breastfeeding uptake: A systematic review of qualitative and mixed-method studies - Rojas-Garcia, Antonio; Lingeman, Sabrina; Kassianos, Angelos P. (My University, 2023)
Recommendations for exclusive breastfeeding are not often adhered to despite the robust evidence of its benefits. This systematic review aims to collate evidence on the attitudes mothers and health care providers have towards breastfeeding interventions to understand what aspects best contribute to acceptability and feasibility.
Keywords: acceptability; behaviour change techniques; breastfeeding intervention; mother; qualitative synthesis; systematic review